6‐(Hetero)arylindolizino[1, 2‐c]quinolines as highly fluorescent chemical space: Synthesis and photophysical properties. (25th June 2020) - Singh, Dileep K.; Kim, Suzi; Lee, Jeong Hwa; Lee, Na Keum; Kim, Jinwoo; Lee, Jeeyeon; Kim, Ikyon
Abstract: A highly fluorescent indolizino[1, 2‐ c ]quinoline with a substituent at the C6 position was designed and synthesized as a new indolizine‐quinoline hybrid structure via a tetracyclic lactam. Various (hetero)aryl groups were introduced at the C6 site of this basic skeleton to display intriguing photophysical properties. Abstract :